Zur Frage pluvialzeitlicher Solifluktionsvorgänge im Hochland von Godjam Highland, Ethiopia - Kuls, Wolfgang; Semmel, Arno (ERDKUNDE, 1965)
During a staty of sometime in the highland of Godjam, northern Ethiopia, devoted to geographical research, the authors of this paper have made a number of observations relating to the question wheter present land forms and soil profiles allow conclusions to be drawn as regards pronounced solifluxion processes due to frost action during the Pluvial period. It emerges, however, that the widely found shallow little valleys as well as the frequently occurring stonelayers may be explained equally well as the result of recent denudation and weathering processes without having to involve frozen ground.